Direction of Trade Statistics Quarterly : September 2013. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2013)
The Direction of Trade Statistics Online service provides data on the value of merchandise exports and imports between each country and all its trading partners. The database includes: total bilateral and multilateral exports and imports aggregated at national or regional group level; data from 1948 at monthly, quarterly, and annual frequencies.